2013
DOI: 10.1299/jbse.8.104
|View full text |Cite
|
Sign up to set email alerts
|

Yielding Phenomena of Aortic Wall and Intramural Collagen Fiber Alignment: Possible Link to Rupture Mechanism of Aortic Aneurysms

Abstract: Estimation of wall strength of the aortic aneurysms is necessary for the prediction of their rupture risk. We previously found a significant correlation between their tensile strength σ MAX and a yielding parameter τ σ , which is the stress when tangent elastic modulus reaches at 63% of the plateau level. This may indicate that the wall strength is estimated from their pressure-diameter relationship. Here we show a possible mechanism of the correlation between τ σ and σ MAX by focusing on alignment of collagen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
2
8
0
Order By: Relevance
“…The same correlation was also reported for aorta root aneurysms . Sugita et al found that the strength correlates significantly with a “yield point,“ namely, a particular stress at the early phase of response . The importance of the latter finding lies in that the yield point is more likely in in vivo stress range.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…The same correlation was also reported for aorta root aneurysms . Sugita et al found that the strength correlates significantly with a “yield point,“ namely, a particular stress at the early phase of response . The importance of the latter finding lies in that the yield point is more likely in in vivo stress range.…”
Section: Introductionsupporting
confidence: 57%
“…It is remarkable that the tension at the maximum curvature location correlates significantly with the strength (Figure ). Sugita et al reported that the ATAA strength correlates strongly with the stress at which tangent elastic modulus reaches 63% of the plateau level. The present finding is in congruence with these reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Martin et al [22] developed a predictive model to assess the in vivo rupture risk of ATAAs based on the measured strength and estimated wall stress. Sugita et al [31] used an inflation test to measure the bi-biaxial properties, and reported a strong correlation between strength and a characteristic stiffness modulus [30]. On the related subject of abdominal aortic aneurysm (AAA) strength, Vorp's group [28,33] measured the tensile strength of AAA tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The same correlation was also reported for aorta root aneurysms [64]. Sugita et al found that the strength correlates significantly with a 'yield point', namely a particular stress at the early phase of response [117,116]. The importance of the latter is that the yield point is more likely in in vivo stress range.…”
Section: Relation Between Strength and Elastic Parameterssupporting
confidence: 65%